Red blood cell transfusion is associated with increased hemolysis and an acute phase response in a subset of critically ill children. Issue 10 (October 2015) - L'Acqua, Camilla; Bandyopadhyay, Sheila; Francis, Richard O.; McMahon, Donald J.; Nellis, Marianne; Sheth, Sujit; Kernie, Steven G.; Brittenham, Gary M.; Spitalnik, Steven L.; Hod, Eldad A.
<x xml:space="preserve">Abstract</x> In healthy adults, transfusion of older stored red blood cells (RBCs) produces extravascular hemolysis and circulating non–transferrin‐bound iron. In a prospective, observational study of critically ill children, we examined the effect of RBC storage duration on the extent of hemolysis by comparing laboratory measurements obtained before, and 4 hr after, RBC transfusion (N = 100) or saline/albumin infusion (N = 20). Transfusion of RBCs stored for longer than 4 weeks significantly increased plasma free hemoglobin (P < 0.05), indirect bilirubin (P < 0.05), serum iron (P < 0.001), and non‐transferrin‐bound iron (P < 0.01). However, days of storage duration poorly correlated (R2<0.10) with all measured indicators of hemolysis and inflammation. These results suggest that, in critically ill children, most effects of RBC storage duration on post‐transfusion hemolysis are overwhelmed by recipient and/or donor factors. Nonetheless, we identified a subset of patients (N = 21) with evidence of considerable extravascular hemolysis (i.e., increased indirect bilirubin ≥0.4 mg/dL). In these patients, transfusion‐associated hemolysis was accompanied by increases in circulating non‐transferrin‐bound iron and free hemoglobin and by an acute phase response, as assessed by an increase in median C‐reactive protein levels of 21.2 mg/L (P < 0.05). In summary, RBC transfusions were associated with an acute phase response and both extravascular and intravascular hemolysis, which were independent of RBC storage duration. The 21% of transfusions that were associated with substantial hemolysis conferred an increased risk of inducing an acute phase response. Am. J. Hematol. 90:915–920, 2015. © 2015 Wiley Periodicals, Inc.